Initiation of rest-grazing during soil thawing improves interspecific relationships and stability of plant communities on alpine grassland - Ma, Kaikai; Hou, Qingqing; Xu, Changlin; Chen, Yanzhu; Yang, Hang; Xu, Jingjing; Yu, Xiaojun (Frontiers in Plant Science, 2024)
Grazing management is essential to maintain the stability of grassland ecosystems. To determine the optimal rest-grazing period of alpine meadow, Rest-grazing for a suitable period can improve interspecific relationships and the stability of plant communities in alpine meadows. In this study, five rest-grazing periods were set based on soil thawing and plant re-greening in this study.established based on the depth of the thawed soil and the coverage of plant regreening. The niche, interspecific relationships, and stability of plant communities at different rest-grazing periodstimes were investigated. The results revealed that rest-grazing during soil thawing resulted in a small niche width and niche overlap of plants, overall positive interspecific associations, and a high stability of plant communities. Delayed rest-grazing time to plant re-greening resulted in a large niche width and niche overlap of plants, overall negative interspecific associations, and a low stability of plant communities. Therefore, rest-grazing in alpine meadows should begin as soon as possible to promote healthy and sustainable utilization of grasslands.